Implementation of POSDCORB Management Functions in the Governance of Protestant Christian Churches in Bali - Putu Michael Uryana; R Tri Priyono Budi Santoso; I Wayan Ruspendi Junaedi; I Gusti Bagus Rai Utama (West Science Journal Economic and Entrepreneurship, 2026)
This study analyzes the implementation of POSDCORB management functions in the governance of the Protestant Christian Church in Bali (GKPB). It responds to the growing demand for religious organizations to be managed not only as spiritual communities but also as accountable, transparent, effective, and sustainable service institutions. A qualitative case study design was employed. Data were collected through in-depth interviews, non-participant observation, and document analysis involving informants from synod, regional, and congregational levels. The data were analyzed through data reduction, data display, thematic coding based on the seven POSDCORB functions, and interpretive conclusion drawing. The findings indicate that planning, organizing, staffing, directing, coordinating, reporting, and budgeting have been implemented in GKPB governance, although their application remains uneven, partially informal, and not fully documented. Planning is participatory and hierarchical, organizing is supported by church structures, leadership is collegial and pastoral, and reporting and budgeting are relatively transparent. Nevertheless, the church still needs clearer job descriptions, stronger leadership regeneration, more consistent cross-sector coordination, standardized reporting, and digitalized administrative and financial systems. This article argues that POSDCORB is relevant for analyzing church governance because it connects managerial systems with service values, congregational participation, and organizational accountability.